Determining the optimal costs on engineering equipment control systems for smart house - O.D. Samarin; E.A. Grishneva (Инженерно-строительный журнал, 2012)
In the paper some candidate solutions of a problem of a decrease of energy consumption in civil buildings were reviewed. The features of implementation of measures on the engineering equipment for smart house were shown. The basic constituents of the working costs were submitted at operation of such object. The dependence of costs change on the depth of engineering measures implementation was investigated. The economically optimum degree of building equipping according to criterion of cumulative discounted costs minimization was detected. The presentation is illustrated by graphic examples and numerical examples of calculations.